Home is where the heart is : the connection between home and the heart transplant journey - Lannon, Heather (2021)
Every year more and more Canadians are diagnosed with heart failure. For some who receive this diagnosis, a heart transplant is required. Heart transplants are not performed in every province in Canada; thus, patients and caregivers must relocate to access transplant care. The research question I sought to answer is: How is home connected to the heart transplant journey? The purpose of my study is to learn from the lived experiences of patients and caregivers, as well as through my lived experience as a caregiver who relocated with a patient to access a heart transplant. To explore these various perspectives two methodologies were used. First autoethnography was used to analyze journal writing which described my experience as a caregiver, who relocated with my husband Jamie, to access a heart transplant. My journals were written during my relocation, which occurred from 2014 to 2017. In total there were 947 journal entries. From my journals, I identified the challenges associated with relocating which include: the stress of finding accommodations, limited finances, a lack of mental health supports, and the challenges associated with being an out of province patient. The supports I found helpful during relocation include my immediate and extended family, and the transplant team. While I did not define home in my journals, it was clear to me that, home meant Newfoundland, my house in Newfoundland, as well as my parents’ house in Newfoundland. Second narrative analysis was used to explore patient and caregiver perspectives of relocating to access a heart transplant. Nineteen interviews were conducted, and during these interviews patients and caregivers identified the challenges they faced during relocation, the supports that made relocation easier, and their definitions of home. The challenges patients and caregivers faced were the same as the ones I had identified in my journals - the stress of finding somewhere to live, financial stress, a lack of mental health support, and the challenges associated with being an ...